La Création de Quinet et la logique du vivant : une épistémologie imaginaire - Séginger, Gisèle (Studia Romanica Posnaniensia, 2018)
Quinet studies the logic of life in natural history, history and the arts from an epistemological viewpoint. He shows interesting similarities between different fields of study, and he explains the specificity of the épistémè of the 19th century. This paper will show the impact of the concept of the unity of knowledge on the writing of Quinet’s book, and the ideological and religious implications.